Evaluation of aquatic macrophyte substrate for the growth of Jucá (Libidibia ferrea) seedlings) (Research, Society and Development, 2020)
It is known that human action, in recent decades, has caused serious consequences to the environment, possibly because the current economic system demands large-scale production and, consequently, a greater use of natural resources. In this context, this study aimed to evaluate the initial growth of Jucá (Libidibia ferrea) as a function of the aquatic macrophyte organic compound (E. crassipes). The treatments were distributed in randomized blocks with three replications, with the experimental units consisting of pots with 2 dm3 of soil and the different combinations of organic compost and soil, the following treatments were composed: T1 = soil; T2 = 95% soil + 5% compost; T3 = 90% soil + 10% compost; T4 = 80% soil + 20% compost and T5 = 70% soil + 30% compost. Ten days after the emergence of the plants, the transplant was carried out, and during the period of 60 days, six readings of plant height and stem diameter were taken to evaluate growth, the first being ten days after transplanting and the following, also , in an interval of ten. AGR and RGR, both for plant height and stem diameter, were similar in all treatments, emphasizing that for T4 and T5 higher heights were observed and in T3 the RGR of the diameter showed more uniform growth.